A study on impact of trust in supply chain management at PETRONAS Gas Berhad / Mohd Amin Zakaria - Zakaria, Mohd Amin (Faculty of Business and Management, 2010)
Supply Chain comprises a worldwide network of suppliers, factories, warehouses, distribution centres and retailers through which raw materials are acquired, transformed and delivered to the end user. Supply chain is a combined system which comprises planning, sourcing, making and development of processes with its constituent parts to include material suppliers, production facilities, distribution centres and customers linked together through the feed forward flow of material as well as feedback flow of information. Am. J. Engg (2009) Supplier is the part of supply chain management. Building trust in supplier is a crucial part in the organization. This study is about to investigate the impact of trust in the supply chain at Petronas Gas Berhad, Plant Operations Diivision, Kerteh. There are two objectives of this research which are to study the impact of trust in supply chain and to examine the most influence factor in trust in the supply chain. This study concentrates on two variables that can contribute or leads to trust in this research are information sharing and partner’s reputation. While, the dependent’s variable is trust in the supply chain management. Data collected was analyzed by using the Statistical Package for Social Science (SPSS). A sample of 100 staffs at PGB (POD) has completed questionnaire. In the chapter four will explain the finding analysis and interpretation in this study. This chapter comprises the reliability analysis, frequency analysis, correlation analysis, and mean analysis. The last chapter in this research will provide useful information to the company as well as to the company’s partner. There are several recommendations given by the researcher. These recommendations is believed by the researcher will help the company to run the supply chain process in the better way that lead to reduce cost and tighter relationship with suppliers.